Analysis of factors related to browning of red sour soup during fermentation - Liu, Zhiqi; Zhou, Xiaojie; Wen, Ming; Gong, Zhouliang; Lin, Bilian; Zhao, Liangzhong; Wang, Jianrong (Frontiers in Nutrition, 2023)
As a traditional fermentation food, red sour soup (RSS) is very popular in China. However, browning is always occurred during the process of fermentation, which influences the sensory quality of RSS and limits its further application. Thus, it is meaningful to elucidate the main factors related to browning during the process of fermentation. Herein, the changes in various factors related to browning from group spontaneous (RSS-SF) and inoculant fermentation (RSS-IF) were determined and analyzed. Firstly, the activity changes of enzymes related to browning indicated that browning of group RSS-SF and RSS-IF during fermentation was not related to enzymatic browning. Secondly, path analysis revealed that the main factors related to non-enzymatic browning of group RSS-SF and RSS-IF were oxidation of polyphenol and degradation of ascorbic acid (Vc). The results of this study not only identifies the main factors associate with browning of RSS, but also gives some clues on how to control the browning of RSS in further study.